Origami shelter - Huang, Guozhu. (2012)
The objective of this project is to design one degree of freedom rigid deployable structures based on kite cross section and build the models of origami shelter with further analysis and testing to meet the requirements for practical application. In the project, three designs of origami shelter are presented according to different cross sections. The first design is based on the kite cross section, while the second design introduces vertical walls into shelter and the third design introduces inclined walls into shelter. For all designs, a basic unit of shelter is built and analyzed with various load tests. And the origami shelter will be constructed by joining several identical basic units.